Pathogenesis-Guided Engineering: pH-Responsive Imprinted Polymer Co-Delivering Folate for Inflammation-Resolving as Immunotherapy in Implant-Related Infections - Costa, Raphael C.; Nagay, Bruna E.; Villa, Javier E. L.; Sotomayor, Maria D. P. T. [UNESP]; Neres, Lariel Chagas da Silva [UNESP]; Benso, Bruna; Aguayo, Sebastian; Sacramento, Catarina M.; Ruiz, Karina G. S.; Spada, Fernanda P.; de Avila, Erica Dorigatti [UNESP]; da Costa, Monique G. [UNESP]; et al. (Wiley, 2024)
Folate (FT) is a suitable targeting ligand for folate receptors (FOLR) overexpressed on inflamed cells. Thus, FT-loaded polymers can be used as FOLRs-targeted immunotherapy to positively modulate the inflammatory process. A novel biodegradable imprinted polymer with a FT delivery mechanism driven by pH changes [PCL-MIP@FT] is designed with molecularly imprinted technology. The pH mechanism is validated in vitro, demonstrating that an acidic environment accelerated and increased the release of FT for a period of 7 days (∼100 µg mL−1). For the first time, FT receptors (FOLR-1 and FOLR-3) are discovered and also overexpressed on activated human gingival fibroblasts, representing a favorable target in the oral environment. Although FT itself does not have antimicrobial effects, the nanomechanical properties of biofilm are changed after topical FT administration. In vivo systemic toxicity of PCL-MIP@FT has been demonstrated to be a safe biomaterial (up to 1.3 mg kg−1). When the PCL-MIP@FT is assessed in the subcutaneous tissue, it promoted an alleviating inflammation and may be able to stimulate tissue repair. The present findings have demonstrated the reliable in vitro and in vivo anti-inflammatory actions of FT-loaded polymer and support its use as a novel drug-free therapeutic platform for modulating and mitigating inflammatory responses in dental implant-related infections.
Keywords: biomaterial; folate; implant infection; inflammation; molecular imprinting